Inspiratory muscle training and aerobic exercise for respiratory muscle strength in myasthenia gravis post-hospitalization- a randomized controlled trial - Chia-Ling Chang; Tien-Pei Fang; Hsin-Mao Tsai; Hui-Chin Chen; Shih-Feng Liu; Hui-Ling Lin; Jui-Fang Liu (BMC Pulmonary Medicine)
Abstract Background Previous studies have demonstrated the positive effects of long-term inspiratory muscle training (IMT) on inspiratory muscle strength and pulmonary function. However, the benefits of IMT with aerobic exercise (IMT + AE) in patients with myasthenia gravis (MG) remain unclear. This randomized controlled trial aimed to assess the impact of the early, 6-week, moderate-intensity interval IMT + AE on pulmonary function, functional capacity, and respiratory muscle strength in patients with MG post-hospitalization. Methods Patients with Discharged MG were randomly assigned to either a control group receiving standard medical management or an intervention group undergoing six-week IMT + AE program. Respiratory status was evaluated using the maximum inspiratory/expiratory pressure (MIP/MEP) and pulmonary function tests. Modified Borg dyspnea scores and a six-minute walk test for functional capacity were also employed. Results Fifty-four participants were assigned to either the control (sixn = 28) or IMT + AE groups (n = 26). At 6 weeks, the IMT + AE group showed significant improvements across all parameters, while the control group only showed notable differences in the modified Borg scale scores and walking distance. MIP improvements were 33.8 ± 36.1 cmH2O in IMT and 22.1 ± 25.8 cmH2O in control groups (P = 0.18). The IMT + AE group improvements were more substantial in MEP, modified Borg scale, and 6-minute walk distance, in addition to forced vital capacity (FVC) and FVC % of prediction (0.21 ± 0.24 L and 6.17 ± 6.01%, respectively), while the control group showed decreased volumes (-0.06 ± 0.30 L and − 1.79 ± 9.69%, respectively). FVC improvement was significant with IMT + AE (0.21 ± 0.24 L) vs. reduction in the control group (-0.06 ± 0.3 L; P = 0.001). Conclusions Implementing six-week moderate-intensity interval IMT + AE effectively enhanced respiratory muscle strength, alleviated dyspnea, improved physical capacity, and increased FVC in patients with MG following hospitalization after discharge. Clinical trial registration The study was registered in The Clinical Trials Clinical Trial (NCT06624345|| https://www.clinicaltrials.gov/ ) on October 12, 2024 (retrospectively registered).